Chapter Itinerari amazzonici in Boccaccio: il retroterra romanzo - Luti, Matteo (Studi e saggi, 2020)
The theme of the Amazons accompanies Boccaccio's vast literary production, from youth to maturity. The essay explores the interactions between texts of medieval french literature and Boccaccio's works; at the same time, it aims to place Boccaccio's works within the Angevin culture of Naples in the fourteenth century.